Pilot monitoring and evaluation of the WHO postpartum family planning compendium mobile application: An in‐depth, qualitative study. Issue 3 (2nd March 2021) - Sonalkar, Sarita; Maya, Ernest; Adanu, Richard; Samba, Ali; Mumuni, Kareem; McAllister, Arden; Fishman, Jessica; Schurr, Danielle; Schreiber, Courtney A.; Kolev, Svetlin; Doe, Roseline; Eluned Gaffield, Mary
Abstract: Objective: To assess the feasibility, functionality and acceptability of a mobile application (app), the World Health Organization (WHO) Postpartum Family Planning (PPFP) Compendium, in clinical care. Method: This prospective qualitative study was conducted among family planning providers routinely delivering PPFP care in Accra, Ghana. We conducted in‐depth interviews at baseline and 3 months after app introduction. We elicited expected technological, psychological and environmental barriers to use, actual use in clinical settings, and feedback for app improvement. With inter‐coder reliability, we analyzed the content of interview transcripts. Results: Twenty providers participated in baseline interviews, and 19 participated in follow‐up interviews. At baseline, providers did not have significant technological barriers to its use and felt the app was acceptable, but were concerned about the appropriateness of using an app during clinical care. At 3‐month follow‐up, 18 out of 19 participants reported using the app weekly, and found the app acceptable for use in clinical care. Providers recommended expanding clinical content and including similar guidance relevant to times outside the postpartum period. Conclusion: Use of a PPFP counseling app to aid family planning providers in clinical care delivery is feasible and acceptable. Providers recommended inclusion of similar guidance relevant to times outside the postpartum period. Synopsis: A mobile application is a feasible and acceptable element of an implementation strategy to improve postpartum family planning outcomes in Accra, Ghana.